P.S.R.Rengasamy College Of Engg for women, Sivakasi (International Journal of Engineering and Computer Science, 2017)
Research on Screen Content Images (SCIs) has become important as they are used frequently in multi-device communication applications. In this project, a study on perceptual quality assessment of distorted SCIs subjectively and objectively is made. A screen image quality assessment database (SIQAD) consisting of 20 source and 980 distorted SCIs is constructed. A subjective quality scores is for estimating which part (text or picture) contributes more to the overall visual quality. The single stimulus methodology with 11 point numerical scale is used as subjective method. Followed by the subjective quality analysis an objective metric is used to measure the visual quality of distorted SCIs. In object quality analysis a weighting strategy method is used to correlate quality of the two regions (text and pictorial) of SCI and provide quality for the entire image.